Treatment of hypercholesterolemia: screening of Solanum macrocarpon Linn (Solanaceae) as a medicinal plant in Benin - Tamègnon Victorien Dougnon; Honoré Sourou Bankolé; Jean Robert Klotoé; Maximin Sènou; Lauris Fah; Hornel Koudokpon; Casimir Akpovi; Tossou Jacques Dougnon; Phyllis Addo; Frédéric Loko; Michel Boko (Mashhad University of Medical Sciences, 2014)
Objective: Hypercholesterolemia is the greatest risk factor for cardiovascular diseases. The present study is conducted to evaluate the lipid lowering activity of leaves and fruits of Solanum macrocarpon, a vegetable, on Wistar rats experimentally rendered hypercholesterolemic by Triton X-100. Materials and Methods: The leaves and fruits were administered (p.o.) for 7 days to rats at doses of 400 and 800 mg/kg of body weight. Atorvastatin was used as reference treatment drug. The data were analyzed by the Brown-Forsythe ANOVA, Dunnett's T3 multiple comparison test, and Dunnett's t test. All tests were done at the 5% significance level. Results: Administration of S. macrocarpon (fruits as well as leaves) resulted in a statistically significant decrease in total cholesterol, LDL-cholesterol, VLDL-cholesterol, and triglycerides in the treated groups compared with the untreated hypercholesterolemic group, regardless of the administrated doses. A significant increase in HDL-cholesterol was observed in the treated groups. Hepatic disorders due to the Triton have been corrected by S. macrocarpon. Conclusions: This vegetable effectively suppresses experimental hypercholesterolemia in Wistar rats, suggesting a protective role in cardiovascular diseases. Its use by individuals at risk should be promoted.